Long-term survival in six cats with mediastinal cysts. Issue 10 (October 2019) - Camero, Corrine M; Neumann, Zachary L; Garrett, Laura D
Case series summary: Mediastinal cysts were diagnosed as incidental findings in six cats evaluated for non-thoracic disease, including staging for historical bladder leiomyosarcoma, flea dermatitis and hairballs, and hyperthyroidism. Radiographically, the cysts appeared as soft tissue opacities cranial to the heart. Ultrasound revealed the masses to be thin-walled, single lumen, anechoic, fluid-filled structures. One cat also had thoracic and abdominal CT performed for cancer staging; the CT revealed a well-defined, fluid-attenuating mass without peripheral contrast enhancement in the cranial mediastinum. Fine-needle aspiration confirmed acellular fluid consistent with a cyst in five cases; in one case the cyst ruptured during aspiration and no fluid was obtained. Post-aspiration, all masses were no longer visible with ultrasound or radiographs. No treatment was recommended for the cysts. Long-term follow-up (2–9 years post-diagnosis) was available in all six cats. The cysts recurred in five cats but were never associated with clinical signs. Relevance and novel information: Mediastinal cysts are an important benign differential for cranial mediastinal masses in cats. Treatment for the cysts does not appear to be indicated. This series also includes the first CT description of this clinical entity.